Exploring the Impact of Video-Based Assignments on Students Knowledge Retention and Insights from Qualitative Analysis - Rahane, Pawan; Shelar, Mahesh; Panchbhai, Mangesh; Kale, Shivaji (Journal of Engineering Education Transformations, 2025)
This research paper delves into the effectiveness of Video-based Assignments (VBA) as a pedagogical tool in improving student retention rates within higher education settings. The study employs a mixed method approach, assessing the student's retention after five months using objective tests for quantitative analysis and a questionnaire with polytomous responses for qualitative analysis. The study was conducted with over 1000 first-year engineering students. Based on the consent agreement respondents gave, 109 responses were recorded and used for research purposes. Quantitative analysis was done using classical statistical theory. Objective test reliability was determined by Cronbach's alpha coefficient, Pearson correlation coefficient and Biserial point correlation. Based on the mean score of 5 by each respondent and positive perspectives of majority of the respondents on VBA as per qualitative analysis it is recommended to equally assign VBA and conventional written assignments to students within higher education settings to enhance knowledge retention, creativity and innovative thinking.